A Medea called Wally: race, madness and fashion in Paul Heyse's novella 'Medea' - Bartel, Heike (Wiley, 2011)
In the extensive tradition of adaptations of the Medea myth in German-speaking literature Paul Heyse’s novella Medea (1898) has been often overlooked. However, the fact that it is the first text to introduce the tragic heroine from classical mythology as ‘black’ gives it particular relevance. This contribution provides an analysis of the text with emphasis on Heyse’s portrayal of the Medea/Wally character at the interface of late nineteenth-century discourses about race, colonial politics, female sexuality and social class.